Perbedaan Metode Latihan Piramida Tunggal dan Ganda terhadap Peningkatan Angkatan Klasik Atlet Angkat Besi - Sahri, Sahri; Sriyanto, Sriyanto; Soegiarto, Soegiarto; Hadi, Hadi (Media Ilmu Keolahragaan Indonesia, 2014)
results pyramid training methods singles and doubles against classical force increase in weight lifters. The experimental quantitative research examines differences in the results of independent variables and the method of training a single pyramid gandadengan dependent variable classical force increase in weightlifting. The population is female athlete weightlifting PPLP Central Java. A sample of 5 athletes with total sampling technique. data collection using pretest and posttest, methods of data analysis using SPSS program. The results of the data analysis performed by t test showed pretest data is obtained t = 0.745 with a significance value 0.510> 0.05, posttest data is obtained t = 0.631 with a significance value 0.573> 0.05, an increase of data obtained t = -1.057 with a significance value of 0.368 > 0.05, which means that the average pretest, posttest, and the increase of the two groups were not significantly different. The conclusions of this study was no significant difference in the improvement of the classical force after getting treatment with a single pyramid laden training methods and double. The methods can be used to practice weightlifting.